Simpson’s paradox: a demographic case study about population dynamics, poverty and inequality - Guimarães, Raphael Mendonça (2021)
Brazil is experiencing a demographic transition marked by regional inequalities. It is possible to assume that aspects related to poverty, development and inequality can reverse the association effects of the demographic transition indicators, typifying a phenomenon known as Simpson's Paradox. The aim of this study was to analyze the effect of inequality, poverty, and social development on the Brazilian population dynamics, verifying the occurrence of Simpson's paradox in the demographic transition. Population data from the Brazilian Demographic Censuses from 1991 to 2010 were used, according to age in Brazil and federation units. The correlation between demographic indicators was evaluated, stratifying the units of the federation into groups according to social indicators. There is an advance of UFs in relation to social indicators, although heterogeneity persists. The transition has been occurring in all FUs, with the distance between them persisting, even though it has been decreasing over the years. Simpson's paradox was observed when the analysis was carried out according to the census year, and according to the social indicator, mainly for the year 1991. The main challenge is to understand how the Brazilian demographic dynamics can be analyzed and to understand how the contextual factors change its rhythm, quantum, and pattern.